Perbandingan Proses SHF & SSF dalam Produksi Bioetanol dari Bonggol Pisang Kepok - Arofah, Kurnia Leni; Amus , Filomena; Kartika W, Fikka; Kartika F, Ayu Chandra (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
The kepok banana hump waste contains 76% of starch and patent production of bioethanol biosphere is biomass ethanol and acts as alternative energy instead of oil fuels. The study aims to determine the comparison of methods of Simultaneous Saccharification and Fermentation (SSF) and Separate Hydrolysis and Fermentation (SHF) %yield and the influence of raw materials masses on %yield. The study uses the process of enzymatic hydrolysis, the enzyme used in the hydrolytic process of Î±-amylase to break starch into a complex sugar with temperature 95ËšC for two hours and the glucoamylase to break the complex sugar into a simple compound of 66ËšC for three hours after which it is sterilized for 30 minutes using an autoclave device to kill bacteria. Then supported to convert sugar into ethanol at temperature. the mass used is 50 and 100 grams and concentrations of Î±-amylase enzymes, glucoamylase, and alcoholics by 10 (b/b) and was then dissented according to the 78ËšC ethanol dedication to get mummified ethanol. Improved results include SHF and %yield methods extracted from raw materials of 6,4% and 1,5% respectively while the kepok banana hump mass. The best group banana from the SHF and SSF methods is 50 grams with an %yield produced by 6,4% and 3,2% respectively.